BIBLIOMETRIC ANALYSIS: HOW THE TREND OF STUDY OF IPS LEARNING IN BASIC EDUCATION IN THE LAST TEN YEARS - Marsini; Bayu Purwo Adhi (RADJA PUBLIKA, 2022)
The purpose of this study is to analyze the trend of learning Social Sciences in Elementary Schools. The focus of the research is to look at the social sciences learning apparatus in elementary schools. This research method uses literature studies through bibliometric analysis. Data search uses publish or perish and Vosviewer applications. The data source was obtained from the Scopus database which obtained 217 articles from the year 2013-2022. The research method uses bibliometric analysis with quantitative methods aimed at classifying data, producing representative summaries, and is recognized as a useful approach for analyzing the performance of journals, institutions, authors, and the characteristics of the research topic. The results showed that trend topic mapping in Social Education Learning research over the past ten years has fluctuated, decreasing from 2013-2018 and increasing in the following year when the Covid-19 pandemic occurred so that it reached its peak in 2020 then slumped until 2022 became a challenge for contribution future researchers to find out how far this topic is developed. The trend topic of e-learning research has the potential to be researched in the future. The use of e-Learning was effective during the Covid-19 pandemic in maintaining student learning outcomes.